Amelioration of sepsis-induced hepatic and ileal injury in rats by the leukotriene receptor blocker montelukast - YEGEN, BERRAK; ERCAN, FERİHA; ŞENER, GÖKSEL (CHURCHILL LIVINGSTONE, 2005)
Background. Sepsis is a generalized inflammatory response, which involves organ systems remote from the locus of the initial infectious insult, involves the release of cytokines and the subsequent formation of reactive oxygen and nitrogen species. Objective: The aim of this study was to investigate the possible protective effect of montelukast, a leukotriene receptor blocker, against oxidative damage in the liver and ileum of septic rats. Methods: Sepsis was induced by cecal ligation and puncture method in female Wistar albino rats. Sepsis and sham operated (control) groups received either saline or montelukast (10 mg/kg, ip) immediately after the operation and at 12 h. Twenty-four hours after the surgery, rats were decapitated and malondialdehyde (MDA) content-an index of lipid peroxidation, glutathione (GSH) levels-a key antioxidant, myeloperoxidase (MPO) activity-an index of neutrophil infiltration, and collagen contents were determined in the liver and ileum. Formation of reactive oxygen species in liver and ileal tissue samples was monitored by using chemiluminescence (CL) technique with luminol and lucigenin probes. Both tissues were also analyzed histologically. Serum lactate dehydrogenase (LDH) and tumor necrosis factor-alpha (TNF-alpha) level were assessed in trunk blood. Results: Sepsis resulted in decreased GSH levels, and increased MDA levels, MPO activity, CL levels and collagen contents in both the liver and the ileum (P < 0.05 - P < 0.001) indicating the presence of the oxidative damage. Similarly, serum TNF-alpha and LDH were elevated in the sepsis group as compared to control group. On the other hand, montelukast treatment reversed all these biochemical indices, as well as histopathological alterations, which were induced by sepsis. Conclusion: Findings of the present study suggest that montelukast possesses an anti-inflammatory effect on sepsis-induced hepatic and intestinal damage and protects against oxidative injury by a neutrophil-dependent mechanism. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: OXIDATIVE STRESS; GENE-EXPRESSION; SEPTIC SHOCK; INFLAMMATION; MELATONIN; DAMAGE; PERITONITIS; GLUTATHIONE; GENERATION; ENDOTOXIN